ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR INDUSTRI DEPARTMENT STORES DAN ADVERTISING - Dian Rudiana; Regina Jansen Arsjah (JURNAL LENTERA BISNIS, 2025)
This study analyzes the factors contributing to financial distress in companies within the department stores and advertising subsectors listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023. Employing binary logistic regression, the research evaluates the impact of liquidity, leverage, and profitability on the likelihood of financial distress. Findings indicate that department stores are vulnerable to consumer behavior fluctuations and intense retail competition, while advertising firms face risks from client dependency and shifting advertising budgets. Liquidity and profitability have a significant negative effect, whereas leverage has a positive effect on the probability of financial distress. The study recommends effective risk management, revenue diversification, and stringent financial monitoring to enhance corporate resilience against economic challenges.